Secondary Subtalar Arthrodesis: Surgical Outcome and Predictors of Functional Outcome and Quality of Life After Bone Block Distraction vs In Situ Technique - Robin Eelsing BSc; Sally Al-Sheikh MD; Jens A. Halm MD, PhD; Tim Schepers MD, PhD (Foot & Ankle Orthopaedics)
Background: The outcome of a secondary subtalar arthrodesis after prior calcaneal fracture has been widely described. However, the surgical treatment has evolved significantly over the past decade, paralleling the shifts observed in primary repair strategies. Therefore, we describe the outcome following a secondary arthrodesis after an intra-articular calcaneal fracture, comparing the in situ (ISA) and bone block distraction arthrodesis (BBDA) techniques. Methods: In total, 339 patients who underwent a subtalar arthrodesis between January 1998 and November 2022 were screened for eligibility. Inclusion criteria were age ≥16 years, having undergone a subtalar arthrodesis following a calcaneal fracture, and a minimal follow-up of 1 year. Exclusion criteria were subtalar arthrodesis before January 2010 and a subtalar arthrodesis within 6 weeks of injury. A total of 259 patients did not meet the inclusion criteria, resulting in the inclusion of 80 patients with 82 fractured calcanei. Results: No significant differences between ISA and BBDA in surgical outcome were seen. Subtalar fusion was achieved in 78 of the patients (95.1%). Additionally, a deep surgical site infection occurred in 6 patients (7.8%). The American Orthopaedic Foot & Ankle Society ankle-hindfoot scale (AOFAS) and Foot Function Index (FFI) scores and the EuroQol–5 dimensions (EQ5D) index were similar between the 2 groups. However, a significantly higher EQ5D-VAS was reported by the subjects who received a BBDA (median [interquartile range], 70.0 [52.0-82.0] vs 81.0 [70.0-90.3], P  = .021). Multiple regression revealed that a higher Böhler angle before the initial fracture reconstruction significantly improved the AOFAS score, whereas the FFI significantly improved by an initial conservative treatment and implant removal after arthrodesis. Finally, increasing age significantly improved the EQ5D index. Conclusion: Our study presents comparable surgical outcomes between ISA and BBDA for secondary subtalar arthrodesis following calcaneal fractures. Functional outcomes, as measured by the AOFAS and FFI scores, were also similar between the 2 techniques, although patients undergoing BBDA reported higher EQ5D visual analog scale scores. Level of Evidence: Level III, retrospective cohort study.